2020
DOI: 10.3389/fmolb.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Voltage-Gated Sodium Channel β3 Subunit Dynamics

Abstract: Voltage-gated sodium (Na v) channels form the basis for the initiation of the action potential in excitable cells by allowing sodium ions to pass through the cell membrane. The Na v channel α subunit is known to function both with and without associated β subunits. There is increasing evidence that these β subunits have multiple roles that include not only influencing the voltage-dependent gating but also the ability to alter the spatial distribution of the pore-forming α subunit. Recent structural data has sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…2 ). V138I has been identified in three cases of SD, but unfortunately it has not been experimentally assessed and so its mechanism of action on Na V 1.5 is unclear (Liu et al., 2014 ), but computer‐simulated mutations in the linker region of β1 have been demonstrated to dramatically alter the orientation of the Ig domain (Glass et al., 2020 ), which could be expected to have deleterious effects on the Na V 1.5–β1 interaction. The β1‐D153N mutation, identified in an individual with AF, significantly attenuated the increase of peak I Na conferred by β1 without altering gating properties (Watanabe et al., 2009 ), suggesting the mutation disrupts the expression and/or trafficking of Na V 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). V138I has been identified in three cases of SD, but unfortunately it has not been experimentally assessed and so its mechanism of action on Na V 1.5 is unclear (Liu et al., 2014 ), but computer‐simulated mutations in the linker region of β1 have been demonstrated to dramatically alter the orientation of the Ig domain (Glass et al., 2020 ), which could be expected to have deleterious effects on the Na V 1.5–β1 interaction. The β1‐D153N mutation, identified in an individual with AF, significantly attenuated the increase of peak I Na conferred by β1 without altering gating properties (Watanabe et al., 2009 ), suggesting the mutation disrupts the expression and/or trafficking of Na V 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular dynamics studies indicated that spontaneous oligomerization of a full-length Na v β3 subunits to a trimer would probably be a very slow process if it occurred in cell membranes. The three TMH of Na v β3 would not interact strongly enough [ 83 ]. In addition, our team also analyzed whether the IgDs of the hNa v β1 subunits could form trimers [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both amino acids have not been exchanged during evaluation across Mammalian species, all of which hints at a pivotal PPI hot spot for Na v α subunits (Figure 7, Table S1 and Figures S1-S9). Glass et al (2020) [83] reasoned that if the hNa v β3 trimer were to interact with the VSDs of the pore-forming α protein in analogy to structurally known hNa v β1, a substantial rearrangement of the IgDs would be necessary. interactions on an atomic level remains one of the most challenging endeavors in structural biology [67][68][69].…”
Section: Ppi Patterns On Na V S Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, they are associated with β-sheet folding, implying a role in determining the integrity of the Ig structure. The D153N variant in β1 constitutes the linker between the Ig and the transmembrane domain, where it can influence the orientation of Ig loop relative to the transmembrane segment (Glass et al, 2020). The transmembrane variant M161T is found within β3 where its transmembrane domain is engaged in the binding to α-subunit (Salvage et al, 2019).…”
Section: Mapping Of Cardiac Arrhythmogenic Variants On Na V β-Subunitsmentioning
confidence: 99%